Peran Guru PAUD terhadap Pencegahan dan Penurunan Stunting di Desa Tongkok Kecamatan Pajar Bulan - Paulenza, Winda; Walid, Ahmad (AT-TUFULA: Islamic Education Early Chilldhood, 2025)
Stunting remains a significant public health issue in Indonesia, particularly in rural areas such as Tongkok Village, Pajar Bulan District. Stunting has long-term impacts on a child's physical growth, cognitive development, and social abilities. This study aims to examine the role of Early Childhood Education (ECE) teachers in preventing and reducing stunting among young children in the village. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews with ECE teachers, parents, and community leaders, as well as documentation of local stunting data. The findings reveal that ECE teachers play a strategic role in raising parental awareness about nutrition, child health, and appropriate parenting practices. Teachers serve as key agents in educating families about balanced nutrition, environmental hygiene, and the importance of monitoring child growth and development. Moreover, their collaboration with local health workers supports the implementation of early detection and intervention programs for children at risk of stunting. In conclusion, ECE teachers in Tongkok Village act not only as educators but also as facilitators, motivators, and catalysts in efforts to prevent and reduce stunting. Sustainable support from both government and the community is essential to ensure that these roles can be carried out effectively and continuously.